STUDY OF SUGARCANE GERMPLASM VARIETIES FOR FLOWERING ABILITY UNDER AGRO-CLIMATIC CONDITIONS OF THATTA - S. Junejo; R. N. Panhwar; B. R. Kazi; A. A. Junejo; U. A. Talpur; G. M. Kaloi; M. Zubair (Journal of Animal and Plant Sciences, 2012)
Field experiments were conducted to observe flowering behavior of different sugarcane varieties under natural environment of Thatta and Ghorabari (coastal belt) sites in Sindh (Latitude 24.5oN). Different sugarcane varieties/genotypes were collected from all available sugarcane germplasm at different Sugarcane Research Institutes of Pakistan and were maintained by simple vegetative propagation (cuttings) method in non-replicated trials during 2008-09 and 2009-10. It was observed that latitude and mean minimum and maximum temperature during flowering inductive phase (September) were within acceptable limits to favour the flowering in sugarcane. However, flowering occurred in most of the cane varieties under natural environment in both sites of Thatta area but the time, intensity and percentage of flowered varieties differed widely between the years of the same environment. The results showed that in sugarcane germplasm planted as plant crop at Thatta during 2008-09, 30.44 percent varieties/genotypes flowered during 2009-10 with intensity ranging from 10.16 to 87.09 percent. In plant crop during the year 2009-10, 21.27 percent sugarcane varieties flowered during 2010-11 with intensity ranging from 6.12 to 66.66 percent and in ratoon crop of the year 2010-11, 12.43 percent varieties flowered with intensity ranging from 17.24 to 90.0 percent. During the same year in plant crop at Ghorabari site, 57.6 percent varieties/genotypes flowered with intensity ranging from 19.64 to 93.47 percent. The sugarcane crop took about thirteen to fifteen month’s period for its complete flowering. The flowering in sugarcane varieties commenced from November and ended up to January. Most of the varieties flowered during the months of November and December. Only a few could flower during January. Moreover, Ghorabari site of district Thatta closer to sea shore was identified as best for profuse flowering in sugarcane.
Keywords: Sugarcane; variety; flowering; time; percentage; intensity; Thatta